Neruda e Gullar: poesia em rebelião na América - Quirino, Ana Maria (2017)
In this thesis, one presents a study of poetics of Pablo Neruda and Ferreira Gullar, defining the political/social themes, developed from these authors, by noting the similarities and differences on the reading of their poems. Considering the characteristics of the works of the poets analyzed, that match poetic talent and political/social engagement, the focus of this study is the “poetry in rebellion”, expression used by the Mexican poet and literary critic Octavio Paz in his book “O arco e a lira”. Studies about lyricism, political poetry, power, Marxism and literature compose the theoretical basis for the development of this thesis. Considering the size of the complete works of each author, as well as the focus chosen, it was necessary to choose a part of the works of each author: from Neruda, one chose to analyze the poems of the book “Canto geral” from 1950; and from Gullar, one chose the texts of the anthology “Toda poesia” (1950-1987). One also read the books of memoirs published by the authors: “Confesso que vivi - memórias” from Neruda; and “Rabo de foguete” from Gullar – where one can find data recorded by both writers, about the social/political context in which the analyzed poetry was written.